Validação do diagnóstico de enfermagem baixa autoestima em adultos com humor deprimido - Castro, Natalia Barreto de (2023)
Depressed mood usually causes significant changes in the individual's self-concept. A specific nursing approach related to personal self-assessment is included in domain 6 - Self-perception, according to the NANDA-International Nursing Diagnoses: Definition and Classification (NANDA-I). In this taxonomy, the low self-esteem (LSE) is represented from two diagnoses focused on the problem, named situational low self esteem and chronic low self-esteem, whose only apparent difference is the temporality related to the manifestation. Thus, the present study verified the structural validity of a single conception for the nursing diagnosis Low Self-Esteem (LSE) by carrying out three consecutive steps: construction of a middle-range theory (MRT), content analysis by judges, and clinical validation. Initially, the MRT seek to define and to explain the elements and clinical processes that lead to the establishment of the diagnostic hypothesis of LSE in adults with depressed mood. For this, 32 studies were selected, which allowed the identification of 14 etiological factors (EF) and seven clinical indicators (CI). Of these results, only seven EF and one CI showed similarities with the original NANDA-I structure. Posteriorly, the findings of the first stage were submitted to content analysis by 100 judges, consisting of 56 nurses, 25 psychologists, and 19 physicians. The content validity of the components of the LSE diagnosis was calculated from the Content Validity Index (CVI). An analysis of the concordance and internal consistency of the judges' evaluations was carried out from values calculated for the S coefficient (agreement) and Cronbach's Alpha (Internal consistency). Of the 19 EC, 12 were validated by the judges. For the CI, 14 of the 20 elements were considered of high relevance. Finally, in the last step, the evaluation of diagnostic elements in clinical practice took place. For this, 142 adults with depressed mood were selected, between 18 and 59 years old, accompanied in a reference hospital in mental health care in the state of Ceará. Descriptive analysis was performed to obtain absolute frequencies, percentages, measures of central tendency and dispersion. The Lilliefors test was adopted to verify the adherence to normality. A Rasch analysis was developed to identify a set of CI that represented an adequate measure for inference for the nursing diagnosis LSE. The accuracy of CI was obtained through latent class analysis. The analysis of EF was performed using logistic regression. The adjusted odds ratios were calculated for each causal factor, considering a 95% confidence interval and a 5% significance level. The estimated prevalence of the diagnosis was 64.91%. The IC “Suicidal ideation” and “Rumination” had the highest sensitivity value (85% and 92%, respectively). The IC “Absence of purpose” and “Excessive search for reassurance” had a specificity value greater than 90%. The set of EF for Low self-esteem influenced the presence of the phenomenon in question, with the exception of the Functional impairment factor. The most significant EF were “Pattern of failures” and “Repeated negative reinforcement”. Therefore, the new LSE configuration may allow nurses to develop more accurate care strategies for individuals with depressed mood.